Deity with lotus stem, gourd, and Japamala - 048 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Cannot identify the sculpture here as Vishnu since the deity is not holding any of the common artefacts of Vishnu.